The impacts of residential construction and property prices on residential construction outputs: an inter-market equilibrium approach - Ma, Le; Liu, Chunlu; Reed, Richard (International Journal of Strategic Property Management, 2017)
Research into the links between construction output and broader economic development has provided valuable references for inducing theoretical, empirical and policy implications. However, the impact of the construction and property markets on the construction output have not been fully addressed yet. This research argues an inter-market equilibrium between residential construction output and the related markets in terms of construction and property prices. Implementing the panel error correction model, longitudinal data of Australian capital cities is used to identify the inter-market equilibrium and associated dynamic patterns across the observed cities. Subsequently, by comparing the simulated and actual residential construction outputs, the estimated findings are evaluated. The inter-market equilibriums in the Australian capital cities appeared in geographic-spatial clusters while the economy-scale-spatial clusters were observed in dynamic patterns.